PENGARUH KUALITAS LAYANAN, KEPERCAYAAN DAN KOMITMEN TERHADAP LOYALITAS NASABAH ( STUDI PADA PD. BPR BANK PASAR KENDAL) - Mulyo Budi Setiawan; ukudi . (Fakultas Ekonomika dan Bisnis, Universitas Stikubank, 2007)
The objective of this research is to tested the influence of service quality, trust and commitment toward satisfaction. Service quality, which tested was the ability of The Region Company People Credit Bank Market Bank Kendal to give all kind of service that needed by the customer of The Region Company People Credit Bank Market Bank Kendal. Service quality including service who gave by The Region Company People Credit Bank Market Bank Kendal involved with how they gave service. Trust represented the convenience to make long term relationship to built positive performance, and commitment represented the development of interorganisational value and the core of long term relationship success, which implicitly or explicitly indicated the deal of exchange function with the partner continuously. With good service quality, perhaps will build trust and commitment, therefore creating customer loyalty. With this loyalty, it can be the beginning of the success of The Region Company People Credit Bank Market Bank Kendal. Data tested and analyze with structural equation model. The result from six hipotetis, showed that one off six hipotetis was not proved (hipotetis: the direct effect service quality to loyalty). This result become recommendation to next research, that to create loyalty, it can not reached directly from service quality, but it must be involve trust and commitment. Keywords : service quality, trust, commitment and loyalty